2019
DOI: 10.1038/s41598-019-40311-4
|View full text |Cite
|
Sign up to set email alerts
|

Plastics in sea surface waters around the Antarctic Peninsula

Abstract: Although marine plastic pollution has been the focus of several studies, there are still many gaps in our understanding of the concentrations, characteristics and impacts of plastics in the oceans. This study aimed to quantify and characterize plastic debris in oceanic surface waters of the Antarctic Peninsula. Sampling was done through surface trawls, and mean debris concentration was estimated at 1,794 items.km −2 with an average weight of 27.8 g.km −2 . No stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(138 citation statements)
references
References 54 publications
4
131
1
2
Order By: Relevance
“…We found a total of 449 pieces of plastic (371 from WSA and 78 from the AP (Lacerda et al., 2019), and from that total, 58 plastics were randomly chosen for metabarcoding analysis, of which 32 were from WSA and 26 from AP. These comprised 25 microplastics (17 plastics in WSA and eight plastics from AP, size range 1–5 mm) and 33 mesoplastic (15 plastics in WSA and 18 plastics from AP, size range 5–74 mm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a total of 449 pieces of plastic (371 from WSA and 78 from the AP (Lacerda et al., 2019), and from that total, 58 plastics were randomly chosen for metabarcoding analysis, of which 32 were from WSA and 26 from AP. These comprised 25 microplastics (17 plastics in WSA and eight plastics from AP, size range 1–5 mm) and 33 mesoplastic (15 plastics in WSA and 18 plastics from AP, size range 5–74 mm).…”
Section: Resultsmentioning
confidence: 99%
“…OTUs within Chytridiomycota, Rozellomycota, Aphelidomycota, Cryptomycota which have been shown to be parasites of several algal groups (Gerphagnon, Colombet, Latour, & Sime‐Ngando, 2017; Kagami, De Bruin, Ibelings, & Van Donk, 2007) including diatoms, were also detected. A number of OTUs were found matching undescribed Aphelidiomycota and Rozellomycota taxa (see Figure ), which are parasites of a range of organisms (Karpov et al., 2014; Letcher & Powell, 2019) and could be parasitizing the dense microalgal biofilms on the surface of plastics (Lacerda et al., 2019; Oberbeckmann et al., 2016). Phylogenies also revealed taxa with affinities within the expanded clade of microsporidia, these obligate parasites (Bass et al., 2018) are likely to be parasitizing protists and metazoans within the biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesoscale and submesoscale eddy turbulence is often represented as a random walk in Lagrangian particle modelling (e.g. Haza et al 2012, Maximenko et al 2018, Lacerda et al 2019, where the turbulent diffusion coefficient has been assumed constant. However, this uniform turbulent diffusion will not be able to capture mixing in areas with varying eddy activity.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The highest levels appeared in the Southern Ocean (Figure 1). Even though it is very remote, Lacerda et al [22] found plastic pollution in surface waters near the Antarctic Peninsula. Around here, in the Palmer Basin (65 • W, 65 • S), SST/t2m was −1.0/−2.9 ± 0.1 • C. Numerous research stations are based on the Antarctic Peninsula and the nearby islands.…”
Section: The Month Junementioning
confidence: 99%